Improving the Ability of Moral and Religious Values Through Singing Ablution Applause for Early Childhood at Early Childhood Education - Sonearti, Zotri; Haryono , Mimpira; Sari , Rika Partika (Jurnal Pendidikan Rafflesia, 2022)
The purpose of this study was to find out how to increase the ability of moral and religious values ​​through singing ablution for early childhood in Mentari early childhood education, to find out how to increase the ability of moral and religious values ​​through singing ablution for early childhood at early childhood education in Mentari Village, Nanjungan Village. Classroom Action Research (PTK) which is focused on classroom conditions or situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were the Mentari Early Childhood Education in Nanjungan Village in class B totaling 18 people. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative descriptive manner with the emphasis being used to determine the process improvement expressed in a predicate, while quantitative data analysis was used to determine the increase in results by using percentages. The conclusion of the research is that the ability to improve the ability of moral and religious values ​​through singing ablution for early childhood in Mentari early childhood is well developed.